(untitled) (Scientific journal of the Fergana State University, 2023)
This article describes the modern methods and techniques of teaching students Chinese based on interactive educational technologies. There is an increase in the effectiveness of education, organized on the basis of interactive educational technologies, student activity. When learning anything, but especially when learning a language, problems arise between the student and the subject being studied, and he can quickly go off the intended goal. To avoid this and facilitate language learning, it is necessary to use an interactive teaching method. Due to the fact that nowadays the study of a foreign language has become more popular, this article shows several types of learning using interactive educational technologies.